1D AND 2D INVERSION OF GEOELECTRICAL DATA FOR GEOTHERMAL EXPLORATION - De Surya, Ramadhyan
The geoelectric method is a method that uses the principle of electric current to investigate the subsurface structure of the earth. This method is done by injecting direct electric current into the earth's surface and then measuring the resulting potential difference, so that the apparent resistivity value is obtained for each measurement. This method can be used for shallow exploration which has a depth of about 300-1000 m, for example for geothermal exploration. This study aims to identify lithology which includes structure, rock type and thickness of rock layers as well as geothermal systems resulting from data modeling of the shclumberger method in geothermal area. Measurements were carried out in 18 geothermal areas. In each area of the geothermal location, measurements are made with measurement trajectories that vary from 2000 to 4000 meters.